The Validity of The Decree of The Regent of Selayar Islands Regarding the Determination of State Houses That Do Not Conform to the Type of State House - Rachmad Aldiansyah; Aan Eko Widiarto; Shinta Hadiyantina (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
The issuance of the Selayar Islands Regent’s Decree regarding the placement of non-Echelon II Civil Servants (PNS) in Category III, Class B State Residences has triggered a vertical conflict of norms with legislation at the central government level. This study aims to analyse the administrative validity of this action and to map out its legal implications for local government and civil servants. The research method employed is a legal-normative approach utilising legislative, conceptual, and case-based methodologies. The findings indicate that the Regent’s Decision is valid (rechtmatig) as it meets the parameters of authority, procedure, and substantive validity through the exercise of proportional discretion (freies ermessen). Following the enactment of Law No. 6 of 2023 on Job Creation, rigid restrictions on discretion have been reduced, meaning this decision effectively breaks administrative deadlock and safeguards state assets without falling foul of abuse of power. Internally, this decision provides legal certainty and protection for civil servants against arbitrariness (willekeur), whilst externally it optimises the collection of fees to enhance local fiscal capacity.